Visual attentional orienting in developing hockey players - Enns, J. T.; Richards, J. C. (Journal of Experimental Child Psychology, 1997)
Covert visual orienting was measured in at 12 and 15 years-old hockey players at two skill levels (low and high), and in college students with no hockey training. Two types of cues were tested at five cue-target intervals (100-850 msec): digits that informed of likely target locations, and abrupt luminance changes that occurred randomly at possible target locations. High-skill 15-yr-olds used the general alerting factors produced by both cues better than the other three groups. Their responses were fastest overall and changed least with cue-target interval. For the information cue, all Ss showed increased benefits and costs as the cue-target interval was increased, but high-skill players had generally smaller orienting effects than low-skill players. For the stimulus cue, all Ss showed an inhibition to targets at cued locations, but high-skill Ss showed greater change in the response time function over cue-target interval. These results support an association between hockey skill and several important aspects of visual attention: sustained alertness, efficient voluntary orienting, and efficient processing of abrupt stimulus events. Implication: In sports where recognition and reaction times are important, practice activities that develop these capacities should be incorporated into skill instruction and should be part of a developmental curriculum in young athletes.